225k views
0 votes
Cot A - cot 2A = cosec 2A

User Webmonkey
by
5.2k points

1 Answer

5 votes

Hello!


Cosec can be represented as csc in this problem.


Identities:

1.
cot 2A =
(cos A)/(sin A)

2.
sin(A - 2A) = -cos(A)sin(2A) + cos(A)sin(2A)

3.
sin(A)= (1)/(csc(A))


The variables A and 2A, can be changed to different variables.



(cos A)/(sin A) -
(cos 2A)/(sin 2A) =
csc 2A (Identity 1)


(-cos(2A)sin(A) + cos(A)sin(2A))/((sin(2A)(sinA)) = csc 2A


(sin(-A + 2A) )/(sin(2A)sin(A)) =
csc 2A (Identity 2)


(1)/(sin(2A)) =
csc 2A (Identity 3)


((1)/(1))/(csc(2A)) =
csc 2A (Simplify)


csc(2A) = csc(2A)


The equation,
cot A - cot 2A = cosec 2A, is a true identity.

User Figar Ali
by
5.6k points